Kepastian Hukum terhadap Objek Jual Beli Tanah yang Dimasukkan dalam Harta Boedel Pailit oleh Kurator - Putri, Olivia Gunawan; Santoso, Budi (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The land sale and purchase agreement is not allowed to be carried out by parties who have existing rules. The application of the balance axis in the land sale and purchase agreement has been stated in the Civil Code (KUHPerdata) in article 1320 paragraph (1). The article wants a balance in a relationship that has been formed by the parties, both the seller and the buyer. At this time there are various new problems that arise, both in terms of the agreement and in terms of the object (land) of the land sale and purchase agreement. As for one of the problems that are often encountered, a land sale and purchase agreement is found, in which case the land as the object of sale and purchase is not entirely voting rights or is not under the control of the seller. The object (land sale and purchase) has been designated as the bankruptcy estate by the curator who has the authority. This research method is a type of library research (library research) using a juridical-normative approach. In this study, based on the title and problem formulation, the researchers used descriptive qualitative research analysis. The results of this study that the sale and purchase of land on objects declared as boedel bankrupt assets has the legal consequence of canceling the sale and purchase agreement, where it does not meet Article 1474, Article 1320, and Article 1330 paragraph (1) of the Civil Code regarding the conditions for the sale and purchase agreement. Legal certainty related to this is the existence of compensation from the seller/bankrupt party to the buyer in accordance with Article 1471 and Article 1243 of the Civil Code. In Article 36 of Law 37 of 2004 concerning bankruptcy and PKPU wherein the object of sale and purchase which is the property of the bankrupt boedel the buyer can be declared a concurrent creditor for this matter from the bankrupt which must also be fulfilled the words of the sale and purchase agreement.